2007
DOI: 10.1016/j.amepre.2007.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Associations of Neighborhood Disorder With Drug Use and High-Risk Sexual Partners

Abstract: Background-On a macrosocial level, neighborhood characteristics have been found to be associated with the prevalence of HIV and other bloodborne and sexually transmitted infections (STIs). The current study used structural equation modeling (SEM) to examine the relationship between neighborhood social and physical disorder and high risk sexual partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
137
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 57 publications
(13 reference statements)
8
137
1
1
Order By: Relevance
“…42 However, studies have commonly used various measures of neighborhood socioeconomic status as indicators of neighborhood influence on drug use. 42---44 Some studies have found links between drug use and subjective measures of "neighborhood disorder" 45 or objective measures such as the percentage of vacant housing. 44 Further studies examining the connection between drug use and urban greening are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…42 However, studies have commonly used various measures of neighborhood socioeconomic status as indicators of neighborhood influence on drug use. 42---44 Some studies have found links between drug use and subjective measures of "neighborhood disorder" 45 or objective measures such as the percentage of vacant housing. 44 Further studies examining the connection between drug use and urban greening are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The inclusion of macro-level indicators acknowledges that HIV/AIDS risk is not the sole result of individual-level characteristics but, rather, a reflection of how structural factors may shape behaviors and create health inequalities. 10,11 Increasingly, researchers have begun to assess how these structural factors are associated with HIV/AIDS risk behaviors in order to create multilevel HIV/STI prevention programs that go beyond traditional, individual-level behavior change efforts.…”
mentioning
confidence: 99%
“…At some point in her life, one in 32 African American women will be diagnosed with HIV (Centers for Disease Control, 2013). Although HIV infection is a biological event and exposure to the virus is primarily facilitated by human behaviors, it has been well documented that its impact is significantly moderated by multiple interrelated factors, such as poverty and its associated issues (Cené et al, 2011;Latkin, Curry, Hua, Davey, 2007;Sharpe, 2012) as well as poor access to testing and health care services (Nearns, Baldwin, & Clayton, 2009;Tello, 2008).…”
Section: Introductionmentioning
confidence: 99%